(untitled) (Global Journal of Human-Social Science, 2018)
This paper investigates the Newspaper Reportage of Foreign Exchange (FOREX) Market in Nigeria 2015-2016. Specific objectives of the study are; to ascertain the prominence given by newspapers to the Nigerian FOREX market, to determine the frequency of coverage, to determine the source of stories and most importantly to find out the level of interpretation of foreign exchange stories. This was achieved through a review of related literature. A content analytical method was adopted for the study. Vanguard, The Sun and The Nation newspapers were purposively selected, and a sample size of 84 editions of the chosen newspapers was analyzed. A total of 144 stories issues was derived from the sample size and used to address the research questions. Findings revealed that there was low prominence given to stories of foreign exchange, this was justified by the frequency 131(91%) stories buried inside pages of the selected newspapers, the frequency of publication had a considerable coverage of 144 stories, the source of stories were mostly from the media which had 87(60%) stories, most importantly the level of interpretation was very low as 120(83%) stories were straight news which is a sketchy report. The study recommends that the foreign exchange market should be adequately covered in various columns like editorials, features, special reports, etc, for a detailed interpretation of the story to readers.